Virulence of Streptococcus mutans: a sensitive method for evaluating cariogenicity in young gnotobiotic rats. - Michalek, S M (1975)
Gnotobiotic rats infected with Streptococcus mutans 6715 at 19 days of age and fed a purified diet (305) containing 5% sucrose developed extensive caries lesions on all molar surfaces within 16 days (35 days of age). Approximately twice as many lesions developed when infected rats were maintained until 45 days of age, whereas noninfected rats did not develop caries when fed diet 305. Gnotobiotic rats infected with S. mutans 6715 and fed a purified diet containing no sucrose (300) until day 25 and subsequently fed diet 305 for 10 days developed lesions similar to rats fed diet 305 for 16 days. Furthermore, rats infected with S. mutans 6715 and fed diet 300 until 45 days of age developed approximately one-half the smooth surface lesions as infected rats fed diet 305 for the same length of time. The level of caries on buccal and proximal molar surfaces in 45-day-old gnotobiotic rats varied when animals were infected with S. mutans AHT, BHT, NCTC 10449, 6715, or LM-7. Animals infected with S. mutans AHT showed more severe lesions on the buccal surfaces than those observed in animals infected with the other strains of S. mutans tested, whereas S. mutans 6715 caused significantly more caries on proximal surfaces. On the other hand, rats infected with S. mutans LM-7 exhibited the lowest level of caries on all molar surfaces of the five strains of S. mutans tested.